The Importance of Systemic Response in the Pathobiology of Blast-Induced Neurotrauma - Cernak, Ibolja (Frontiers in Neurology, 2010)
Due to complex injurious environment where multiple blast effects interact with the body, parallel blast-induced neurotrauma is a unique clinical entity induced by systemic, local, and cerebral responses. Activation of autonomous nervous system; sudden pressure-increase in vital organs such as lungs and liver; and activation of neuroendocrine-immune system are among the most important mechanisms that contribute significantly to molecular changes and cascading injury mechanisms in the brain. It has been hypothesized that vagally mediated cerebral effects play a vital role in the early response to blast: this assumption has been supported by experiments where bilateral vagotomy mitigated bradycardia, hypotension, and apnea, and also prevented excessive metabolic alterations in the brain of animals exposed to blast. Clinical experience suggests specific blast-body-nervous system interactions such as 1) direct interaction with the head either through direct passage of the blast wave through the skull or by causing acceleration and/or rotation of the head; and 2) via hydraulic interaction, when the blast overpressure compresses the abdomen and chest, and transfers its kinetic energy to the body’s fluid phase, initiating oscillating waves that traverse the body and reach the brain. Accumulating evidence suggests that inflammation plays important role in the pathogenesis of long-term neurological deficits due to blast. These include memory decline, motor function and balance impairments, and behavioral alterations, among others. Experiments using rigid body- or head protection in animals subjected to blast showed that head protection failed to prevent inflammation in the brain or reduce neurological deficits, whereas body protection was successful in alleviating the blast-induced functional and morphological impairments in the brain.